Empirical evidence of trade credit uses of Brazilian publicly-listed companies - Bandeira, Márcia Lima (2008)
This research provides empirical evidence on the use of trade credit as either a substitution or a complement to bank debt for listed companies in Brazil, controlling for the firms reputation, as stated by Alphonse, Ducret and Séverin (2006). The sample consists of 263 publicly-listed companies for 2006. Our findings support all three hypotheses. We provide evidence that trade credit may be used as a signal for the firm’s quality.